Sicily, Not Italy - Salmeri, Claudio (Review of International American Studies, 2017)
Claudio Salmeri Faculty of Philology University of Silesia in Katowice Sicily, Not Italy Abstract: Since the American continent became a part of the European imagination, it has always been seen to represent freedom. Especially after 1776, when the American democratic “experiment” giving rise to the United States proved durable, America became a source of social and political inspiration to generations of Europeans and non-Europeans alike. Unsurprisingly, also in the Italian context, the catalog of ways in which American values have been “translated into Italian” and adapted to Italy’s cultural space seems to be ever-growing. Yet, even though the cultural transfer dates back to Christopher Columbus, it is especially since the outbreak of World War II that Italy has been markedly influenced by intellectual and material values generated in the US. At some point, the fascination with the US soared to such a level that, incredibly as it may sound, one of the most iconic provinces of Italy would begin to imagine itself as the forty-ninth state of the US long before Alaska and Hawaii gained their present-day status: in Sicily, the American fascination seems never to abate.